Atlas of the world's religions - Smart, Ninian 1927-2001; Denny, Frederick Mathewson; Heritage, Ailsa (Oxford University Press, 2007)
This superbly illustrated reference work remains the only comprehensive visual guide to the world's religious traditions. With text by leading experts and lavish photography, thematic maps, tables, and charts, the Atlas of the World's Religions, second edition ranges from the travels of the Buddha to the geographical distribution of modern indigenous faiths, providing a full and informative picture of world religion, both past and present